Números Mórficos - Ferreira, Ronaebson de Carvalho (2015)
Morphic numbers are numbers related to the form and, somehow, they establish a conception of beauty, aesthetics and harmony. These numbers have important of applications in various branches of knowledge, such as geometry, arithmetic, architecture, and engineering. There are only two morphic numbers, the golden number and the plastic number. The rst one has been studied since ancient Greece, and the second one has only become a subject of interest in the twentieth century, what makes the plastic number a relatively new branch of research. In this work, we will analyze a data collection concerning arithmetic, algebraic or geometric properties of these numbers, by establishing a straight relation between the morphic numbers and the Fibonacci and Padovan sequences.